Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.14218/jcth.2014.00008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Transient Elastography in the Diagnosis of Liver Fibrosis: an Expert Panel Review and Opinion

Abstract: Liver fibrosis evaluation is pivotal for treatment decisions and prognosis assessment in patients with chronic liver disease. Liver transient elastography (TE) is a newly developed non-invasive technique for diagnosis of liver fibrosis. It can assess the state of liver fibrosis by liver stiffness measurements, and offers better performance for the diagnosis of liver cirrhosis than serum biological markers. It has now been approved for clinical use in China. The aim of this review is to provide a guide for clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…The optimum cut-off value for F ≥2 was 6.6 kPa in the present study, which was slightly lower than the values for NAFLD (6.9 kPa) and CHB patients (7.2 kPa). However, the optimum cut-off values for F ≥3 and F=4 were 8.7 kPa and 10.9 kPa, which were intermediate values between those for NAFLD (8.4 kPa and 10.3 kPa) and CHB patients (9.4 kPa and 12.2 kPa) [24, 26, 29]. This variation may be explained by the degree of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The optimum cut-off value for F ≥2 was 6.6 kPa in the present study, which was slightly lower than the values for NAFLD (6.9 kPa) and CHB patients (7.2 kPa). However, the optimum cut-off values for F ≥3 and F=4 were 8.7 kPa and 10.9 kPa, which were intermediate values between those for NAFLD (8.4 kPa and 10.3 kPa) and CHB patients (9.4 kPa and 12.2 kPa) [24, 26, 29]. This variation may be explained by the degree of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study indicated that hepatic steatosis could influence the architectural structure of the liver, potentially changing the propagation time of the vibratory wave through the liver [30]. Statistical analysis indicated that cut-off values with a PLR >10.0 offer sufficient confidence to confirm the diagnosis, while an NLR <0.1 provides enough confidence to exclude the diagnosis [29]. In our study, the cut-off value of 10.9 kPa for assessing cirrhosis had a PLR of 14.9 and an NLR of 0.08.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, TE has been endorsed as an alternative to liver biopsy by international guidelines in guiding clinical management of chronic liver disease, including NAFLD [ 11 , 32 ]. The diagnostic performance for NAFLD fibrosis was excellent using a cut-off value of 9.6kPa, with a positive likelihood ratio (PLR) of 8.9 and the AUROC of 0.93 for ≥F3 fibrosis [ 18 ]. Therefore, TE may be a valid and accurate modality in assessing NAFLD fibrosis in a real-world community-based setting where liver biopsy is not practical for all subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroscan examination was performed at the same study visit. We used increased controlled attenuated parameter (CAP) value of more than 248 dB/m to define the presence of �S1 hepatic steatosis and Liver Stiffness Measurement (LSM) of 9.6 kPa or more for � F3 liver fibrosis [18,19]. Performance of Fibroscan was based on manufacturer's recommendations.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation